Answer: $C$
Given: $2f(x) + 3f(-x) = 15 - 4x \tag{1}$
Substitute $x$ with $-x$, in the above question, we get:
$2f(-x) + 3 f(x) = 15 +4 x \tag{2}$
Multiplying equation $(1)$ with $3$ and equation $(2)$ with $2$, we get:
$6f(x) + 9f(-x) = 45-12x \tag{3}$
and,
$4f(-x) + 6f(x) = 30 + 8x \implies 6f(x) + 4f(-x) = 30+8x \tag{4}$
Subtracting equation $(3)$ and $(4)$,we get:
$5f(-x) = 15-20x $
Now, substitute, $x = -2$, we will get $f(2)$:
$5f(2) = 15 - 20*-2 \implies 5f(2) =55 \implies f(2) = \bf{11}$
$\therefore 11$ is the correct answer.